Assessment of past and future land use/cover change over Tordzie watershed in Ghana - Nyatuame, Mexoese; Agodzo, Sampson; Amekudzi, Leonard Kofitse; Mensah-Brako, Bismark (Frontiers in Environmental Science, 2023)
Land use/cover change (LULC) has been identified as the main driving force of global change. The study investigated LULC in Tordzie watershed in Ghana and predicted the future development. Supervised classification procedure was applied to Landsat images of 1987, 2003 and 2017. Cellular Automata –Markov model embedded in IDRISI 17 software was employed to model LULC for the years 2030 and 2050. The trend of land use/cover change was exploited from 1987 to 2003, from 2003 to 2017 and projected to 2030 and 2050. Settlement and crop land respectively increased from 2.68 % and 16.46 % in 1987 to 3.65 % and 53.47 % in 2003 and finally to 20.61 % and 58.52 % in 2017. Vegetation cover declined from 23.2 % in 1987 to 13.9 % in 2003 and finally to 11.3 % in 2017. The annual rate of change was determined. In 2030 and 2050, the dominant land use type will be crop land (56 %). However, it decreased between 2017 and 2030 by -1.73 %. The findings of the study are very relevant to land and water resources planners, policy formulators and implementers, environmental and climate change advocates. Sustainable land use policy and its implementation is recommended.